Effects of Snow Grain Shape and Mixing State of Snow Impurity on Retrieval of Snow Physical Parameters From Ground‐Based Optical Instrument. Issue 15 (8th August 2020) - Tanikawa, T.; Kuchiki, K.; Aoki, T.; Ishimoto, H.; Hachikubo, A.; Niwano, M.; Hosaka, M.; Matoba, S.; Kodama, Y.; Iwata, Y.; Stamnes, K.
Abstract: We proposed new snow grain model and snow impurity mixture models for the purpose of accurate retrievals of snow grain size and concentration of light‐absorbing particles (LAP) in snow from the optical remote sensing data. Two kinds of ice crystal models, irregularly shaped Voronoi columns, and Voronoi aggregates were employed. LAP can be captured by the snow through two processes: dry and wet deposition. Two different snow impurity mixture models were proposed. One is an external mixture model. We employed a coated sphere model in which soot were hydrophilic particles to represent a hygroscopic property of aerosol and assumed the hydrophilic soot particles to be externally mixed with snow particles. The other is an internal mixture model. We employed a dynamic effective medium approximation method in which soot particles were randomly located within snow particle with any size distribution and number concentration. Validation of these models is conducted using a ground‐based spectral radiometer system with in situ measurement data. For snow grain size retrievals, a Voronoi mixture model seamlessly representing a geometrical shape and an optical properties of various snow types can provide accurate retrievals. For the retrieval of LAP concentration in snow, employing different mixing state models depending on season and measurement site gives accurate results. We also discussed the uncertainty of retrieved snow parameters on the surface slope involved in the retrieval accuracy. These models are expected to be useful for advanced airborne/satellite remote sensing and climate studies via radiative transfer modeling in the atmosphere‐snow system. Key Points: New snow grain models for accurate retrievals of snow grain size and concentration of light‐absorbing particles (LAPs) in snow are proposed Two kinds of ice crystal models, irregularly shaped Voronoi columns and aggregates can be represented from small to large snow grain size Employing different models in LAP mixing state (internal or external mixture model) depending on season and location gives accurate retrievals